Sixth Five Year Plan (Approved) 1980-85 Government of Haryana - Planning Commission (Planning Commission, 1982)
Haryana State came into existence as a separate State on the 1st November, 1966,_whenafter independent programmes were initiated to develop this region which was hitherto relatively backward. In this chapter stock of the various achievements has been taken to locate the shortcoming so that better efforts may be made to chart the course of future plan development of the State in conformity with the reoriented national strategy for the Sixth Five Year Plan.
Government of Haryana, Planning Department